Do Financial Constraints Matter for Foreign Market Entry? – A Firm-Level Examination - Joel Stiebale (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2008)
Recent theoretical and empirical contributions stress the importance of financial development for international trade. This paper investigates whether financial constraints matter for foreign market entry at the firm level using dynamic panel data techniques. The empirical framework is applied to a panel of French manufacturing firms over the years 1998-2005. Although financial indicators are significantly correlated with export status and export share, there is no evidence that financial constraints have a direct impact on foreign market participation or sales in foreign markets once observed and unobserved firm heterogeneity is controlled for. This result also holds for subgroups of firms that are more likely to face financial constraints and industries that are more dependent on financial factors.
Keywords: F14; D92; C23; 330; Exports; financial constraints; sunk costs; Exportindustrie; Verarbeitendes Gewerbe; Internationale Markteintrittsstrategie; Verschuldungsrestriktion; Sunk Costs; Frankreich